Universidades federais na pandemia da Covid-19: A falta de acesso à internet interdita mesmo o ensino? - Remi Castioni; Adriana Almeida Sales de Melo Melo; Paulo A. Meyer M. Nascimento; Daniela Lima Ramos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper discusses the interruption of teaching and learning activities at Brazilian federal universities at the time the Covid-19 pandemic broke out, as well as the extent to which the lack of access to the internet would prohibit remote resumption of those activities. Political-educational strategies in line with WHO recommendations are addressed. Then the universities' immediate responses to the necessary suspension of face-to-face activities are debated. Finally, official data are used to estimate the numbers of higher education students without internet access at home. Given that 98% are connected to the internet, it is rather a matter of ensuring internet access and e-skills to those few who are not - there seem to be no consistent justifications for persisting with the interruption. Emergency remote teaching (ERT) boosts amid the pandemic but it is blended learning methodologies that tend to perpetuate in the aftermath of Covid-19 - sooner or later requiring new attitudes and strategies from the Brazilian federal universities. Universalizing internet access among its students does not suffice, but it is a necessary and first-order condition to make ERT and blended learning possible at the universities. Along with the considerations about the resumption of classes during the pandemic and about the future of federal universities beyond the Covid-19 pandemic, the main contribution of this text is to present estimates of the size of the problem of lack of internet access at home among university students. As the estimates suggest, that is too small a problem to justify the complete and prolonged interruption of teaching and learning activities.
Keywords: I21; I23; I28; 330; higher education; access to the internet; blended learning; Covid-19